PP.37.26: ASSOCIATION BETWEEN ARTERIAL STIFFNESS AND SELF-PERCEIVED SNORING AND SLEEP APNEA IN A LARGE COHORT OF PHARMACOLOGICAL UNTREATED SUBJECTS. (June 2015) - Cicero, A.F.G.; Morbini, M.; Rosticci, M.; Cagnati, M.; Grandi, E.; D'Addato, S.; Borghi, C.; Group, Bhs
Abstract : Objective: The correlation of both obstructive sleep apnoea syndrome (OSA) and snoring with cardiovascular risk is well known, but its investigation is complex and unsuitable for studying large cohorts of subjects. The primary aim of this study was to evaluate if self-reported snoring and sleep apnoea are significantly related to arterial stiffness. Design and method: We evaluated 1328 subjects selected from the last survey of the Brisighella Heart Study. Snoring and sleep apnoea were investigated asking the subjects if they were aware to snore during the night and if this was associated to episodes of apnoea. A full set of clinical and hematochemical parameters were evaluated, while augmentation index (AIx) and other hemodynamic parameters were recorded with the Vicorder® apparatus. A logistic regression analysis was performed to identify independent associations between selected parameters and reported snoring and apnoea. Results: Logistic regression analysis showed that snoring was independently associated with WC (OR = 1.04, 95% CI 1.03 – 1.06) and AIx (OR = 1.02, CI 1.01 – 1.04). Apnoea was found to be independently associated with WC (OR = 1.04, CI 1.01 – 1.06), PP (OR = 0.97, CI 0.95 – 0.99), GGT (OR = 1.01, CI 1.01 – 1.02) and HDL (OR = 0.97, CI 0.95 – 0.99). Dividing the sample by sex, we registered in males the independent association of snoring with AIx (OR = 1.04, CI 1.01 – 1.07), and of apnoea with PP (OR = 0.97, CI 0.94 – 0.99), GGT (OR = 1.01, CI 1.01 – 1.02) and HDL (OR = 0.96, CI 0.93 – 0.99). As for females, snoring was independently associated with WC (OR = 1.05, CI 1.03 – 1.07) and visceral adiposity index (VAI) (OR = 1.01, CI 1.01 – 1.02), and apnoea was associated with HC (OR = 1.09, CI 1.04 – 1.15) and PP (OR = 0.97, CI 0.93 – 0.99). Conclusions: Arterial stiffness is positively associated with self-reported snoring in a whole patient sample, while dividing the sample by sex this association is only maintained for males. Self-reported apnoea is negatively associated with PP.